Developing a Test to Measure the Parsing Skill of Student in Language of Arabic Department (Journal Of Educational and Psychological Researches, 2024)
The current research aims to develop a test to measure the parsing skills of students in Arabic language departments in Iraqi universities. To achieve this, the researchers developed a test consisting of 40 multiple-choice items. The test was presented to a group of experts to ensure the validity of the test. The test was applied to a survey sample of 20 male and female students. It was found that the expressions were clear to them and that the average response time was 50 minutes, and to verify the psychometric indicators To test (reliability, discrimination, difficulty, effectiveness of incorrect alternatives, the relationship of the item to the total score of the test), the researcher chose a proportional, stratified random sample of (340) male and female students from the Arabic language departments in public and private colleges. Using appropriate statistical methods, the results showed that two items were excluded for not obtaining the degree of distinction that is statistically significant. Thus, the test is ready for use.